VISCOELASTIC AND PROCESSING EFFECTS ON THE FIBER-MATRIX INTERPHASE STRENGTH .1. THE EFFECTS OF LOADING RATE, TEST TEMPERATURE, FIBER SIZING AND GLOBAL STRAIN LEVEL - SANCAKTAR, E; TURGUT, A; GUO, F (Gordon Breach Sci Publ Ltd, 1992)
[Abstract Not Available]
Keywords: FIBER-MATRIX INTERPHASE; SINGLE-FIBER FRAGMENTATION TEST; FIBER SIZING; RATE-TEMPERATURE-INTERPHASE THICKNESS SUPERPOSITION; NONLINEAR VISCOELASTIC STRESS ANALYSIS; CRITICAL FIBER FRAGMENT SIZE